Perancangan Tata Letak Gudang Berdasarkan Volume Penyimpanan Bahan Baku dengan Metode Corelap - Ecep Ajang Nurjaman; Luthfi Nurwandi (Jurnal Riset Teknik Industri, 2023)
Abstract. The focus of this paper is on the storage of bread raw materials in warehouses. Based on the results of observations and interviews. In the current storage of raw materials, there are gas raw materials that are brought closer to food raw materials, so if it left unchecked without providing a distance, therefore the food raw materials that are produced into bread that is ready to be marketed will contain poison. Based on the phenomena that occur, it is required to design a proposed tata letak using the ABC classification inventory with the CORELAP algorithm approach (Computerized Relationship Tata letak Planning). The aim of the study was originally intended to focus to determine the classification of raw materials using ABC inventory. After determining the classification of raw materials, the data is used as the basis for determining ARC (Activity Relantionship Chart). Because basically the determination of the ABC inventory classification uses costs, but in this study it does not use a cost assessment because it uses the CORELAP algorithm. Based on the processing of the data revealed that, there are several proposed raw material warehouse tata letaks obtained from the results of calculations using the CORELAP algorithm and CORELAP simulation. The layout that pays attention to the production process has a material spacing of 64,6 mm, the layout based on usage volume has a material spacing of 61,6 mm, the layout based on usage frequency has a material spacing of 65,6 mm, and the current layout has a material spacing of 76,6 mm. Therefore, the best distance in the proposed layout design is found in the tata letak design based on the usage volume of 61,6 mm. Abstrak. Penelitian saat ini berfokus pada penyimpanan bahan baku roti di gudang. Berdasarkan hasil observasi dan wawancara. Penyimpanan bahan baku saat ini terdapat bahan baku gas yang didekatkan dengan bahan baku makanan, sehingga apabila dibiarkan begitu saja tanpa memberikan jarak maka bahan baku makanan yang diproduksi menjadi roti yang siap dipasarkan akan mengandung racun. Berdasarakan fenomena yang terjadi, diperlukan peranacangan tata letak usulan dengan menggunakan klasifikasi ABC inventory dengan pendekatan metode algoritma CORELAP (Computerized Relationship Tata letak Planning). Penelitian yang dilakukan merupakan penelitian kuantitatif. Tahap awal dalam merancang tata letak pada penelitian ini adalah menentukan klasifikasi bahan baku dengan ABC inventory. Setelah menentukan klasifikasi bahan baku maka data tersebut dijadikan dasar untuk menentukan ARC (Activity Relantionship Chart). Karena pada dasarnya penentuan klasifikasi ABC inventory ini menggunakan biaya, namun pada penelitian ini tidak menggunakan kajian biaya karena menggunakan algoritma CORELAP. Berdasarkan pengolahan data terdapat beberapa usulan tata letak gudang bahan baku yang didapatkan dari hasil perhitungan menggunakan algoritma CORELAP dan simulasi CORELAP. Tata letak yang memperhatikan berdasarkan proses produksi terdapat jarak material sebesar 64,6 meter. Tata letak berdasarkan volume pemakaian terdapat jarak material sebesar 61,6 meter. Tata letak bedasarakan frekuensi pemakaian terdapat jarak material sebesar 65,6 meter. Tata letak saat ini terdapat jarak material sebesar 76,6 meter. dengan itu jarak terbaik pada perancangan tata letak usulan terdapat pada perancangan tata letak berdasarkan volume pemakaian sebesar 61,6 meter.